The Late Carboniferous Triplosoba pulchella is not a fly in the ointment but a stem‐mayfly. (8th October 2014) - BÉTHOUX, OLIVIER
Abstract The Late Carboniferous Triplosoba pulchella (Brongniart, 1893) was regarded by most authors as a stem‐mayfly. Contrary to this, it was related to the extinct 'palaeopteran' order Diaphanopterodea in the most recent revision of the species. The only available specimen of the species is re‐investigated using various manual and computer‐assisted optical techniques. New data are presented and compared with previous data. The reasoning underlying the 'Diaphanopterodea hypothesis' is found to be deficient due to incomplete observations. Moreover, this hypothesis requires multiple character conflicts within Diaphanopterodea. Instead, the '(stem‐)Ephemeroptera hypothesis' is favoured. The occurrence of a forked RP2, observed in one hindwing of T. pulchella (RP2 is simple in the other hindwing, and incompletely preserved in forewings) is a strict apomorphy of the group. It is also shown that the species possessed what is interpreted as an early state of the costal brace. Other observations do not contradict this placement, which is overall more consistent than an assignment to the Diaphanopterodea. This contribution demonstrates the importance of long‐term conservation of natural history collections, allowing new investigation techniques to be applied in the future.